Inﬂuence of the cavosurface angle on the marginal leakage of Class II composite resin restorations - Quitero, Mayra Fidelis Zamboni; Azevedo, Cynthia Soares de; Luz, Maria Aparecida Alves de Cerqueira; Matos, Adriana Bona (Clinical and Laboratorial Research in Dentistry, 2014)
Objective: The aim of this study was to evaluate, in vitro, the infl uence of the cavosurface angle preparation on the leakage of Class II composite-resin restorations. Methods: Fifteen sound human third molars were sectioned parallel to their long axis through the secondary groove in the buccolingual direction. The roots of the tooth halves thus obtained were embedded in acrylic resin, and Class II proximal slot cavities were prepared. The thirty specimens were then randomly divided into three groups, as follows: G1, bevel preparation; G2, chamfer preparation; G3, butt joint (no preparation on the cavity margin). Composite resin (Z350 XT) was incrementally placed in all cavities. After thermal (5000 cycles, 5°C to 55°C) and mechanical cycling (50000 cycles, 50 N), the specimens were sealed, infi ltrated with 2% methylene blue (4 h, 37°C) and sectioned in halves, which were microscopically analyzed and scored based on a scale. Statistical analyses were performed using the Kruskal-Wallis and Student-Newman-Keuls tests (α = 0.05). Results: G1 (bevel) presented signifi cantly lower microleakage than G2 (chamfer; p = 0.0158) and G3 (butt joint; p = 0.0448). There was no statistically signifi cant difference between G2 and G3 (p = 0.6844). Relevance: The results of this in vitro study suggest that a bevel preparation is able to decrease microleakage in Class II composite-resin restorations.